Problematika Pernikahan Beda Agama: Antara Konsep dan Praktek di Masyarakat - Rifqiawati Zahara; Makhfud (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
Interfaith marriage is not a new thing anymore. In Indonesia, interfaith marriages have been met by many from various social circles, ranging from public figures, officials, to ordinary people. This thing that is considered normal does not necessarily justify or ignore interfaith marriages, but instead often becomes the main controversy in Islam. This paper will describe the meeting point between the rules of Law no. 1 of 1974 which is considered not to accommodate interfaith marriages and provisions in the Qur'an and Hadith which are the guidelines for the Muslim community. In addition, this paper will also show how the practice of interfaith marriages among the community and the impacts they face. Thus, this paper aims to describe the phenomenon of interfaith marriage so that there are new treasures in reinforcing interfaith marriage laws in terms of state and religious rules.